Maternal Mortality in the District of Uzumba in Zimbabwe - Maybe Zengenene (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
Maternal mortality is among the neglected problem in the District of Uzumba, Zimbabwe. This qualitative study therefore, explores the patriarchal hegemonies embedded in the socio-cultural harmful practices, traditions, beliefs, values and norms associated with maternal mortality in Uzumba district. These have been neglected in the reduction initiatives of maternal mortality. The originality of this study lies in the use of primary data through interviews and observation methods on the key informants and significant. Snowballing technique was employed in this study to select the key informants and significant others. The study have also benefited from the proliferation of secondary data on the social phenomena of maternal mortality across the globe. The results of the study showed that, despite the medical related causes of maternal mortality, the non-medical aspects such as patriarchal hegemonies in the socio-cultural practices, beliefs, traditions, norms, values and perceptions play a significant role in escalating maternal mortality especially in Uzumba district, Zimbabwe. The article therefore, recommends that maternal mortality reduction needs more of a holistic approach of medical and non-medical initiatives as it is still the major problem in Zimbabwe’s rural communities. Therefore, maternal mortality can be addressed and reduced within the socio-cultural context as shown in Uzumba district, Zimbabwe.